Personality Traits on Persistent Depressive Disorder - Torres, Ana (2018)
Evidence emerged for the HEXACO Model, summarized the domains of personality in six dimensions. The difficulties associated with the diagnosis of dysthymia have raised questions in maintaining in mood disorders. Given the literature review and defending a modification in the structural model of personality, this study proves the importance of a preliminary study of the psychometric properties of HEXACO in a Portuguese sample. It is important the exploration of personality traits in a clinical population diagnosed with Persistent Depressive Disorder. The sample, for the first study, consisted of 118 women and 48 men aged 18 to 57 years (M=26.21, SD=10.23). The study 2 includes participants belonging to the clinical group (M=48.33, SD=10.23) and nonclinical group (M=41.23, SD=9.63) all female aged between 23 and 63 years. The instruments used for the study were the HEXACO-60, NEO-FFI-20 and PHQ-9. The results demonstrate that the HEXACO-60 has satisfactory psychometric properties that make it a suitable tool to evaluate the personality, presenting high correlations with NEO-FFI and a higher internal consistency. It is also verified that there are significant correlations between depressive symptoms and personality traits. Although this analysis is preliminary with regard to psychometric study of the assessment tool HEXACO-60 personality, the statistical analysis of the instrument showed that it has adequate psychometric properties proving to be an appropriate tool to evaluate the constructs of personality. We conclude that there is evidence to suggest the need for reformulation of the diagnosis of persistent depressive disorder.